Cyclic extrusion compression back pressure technique for hot forging process in direct recycling of aluminium 6061 machining chip - Shahrom, Mohd Syahmi; A. R., Yusoff (Elsevier Ltd, 2017)
Direct recycling is an alternative method of recycling waste aluminium chips without melting the materials, unlike in the conventional recycling technique. A compaction stage is the most crucial stage of direct recycling that significantly affects mechanical properties and microstructure. One problem in direct compaction is low billet density. This study aims to introduce a cyclic extrusion compression back pressure technique for improving billet density, which affects the hardness, particle size and chip boundaries of aluminium alloy 6061 chips during direct recycling of the hot forging process. The experiment design was used as a tool to conduct experiments based on process parameters, such as pressure, back pressure, number of cycles and holding time. A normal compaction technique was used to compare the billet density with the current technique. After the hot forging process, the cyclic porosity and hardness were compared with the original billet material before machining, and the final chip size and boundaries were also analysed. Pressure was identified as the most significant factor affecting the properties of billet density and cyclic hardness. This shows that the current compaction technique can improve billet density by up to 12.11% compared with the direct compaction technique. Consequently, this technique can improve 7% cyclic density and an almost similar hardness as the original billet before machining AA6061. These results are represented by the fine particle size and grain boundaries to improve hardness when the densification is increased. In conclusion, the cyclic extrusion compression back pressure technique successfully improved the hot forging product in the direct recycling process of aluminium chips